2013
DOI: 10.11607/ijp.3302
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Accuracy of CAD/CAM Titanium and Ceramic Superstructures for Implant Abutments Using Spiral Scan Microtomography

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
1
19
0
2
Order By: Relevance
“…With this technique the marginal gap can easily be defined and measured, although measurements will only be carried out in the defined slices. Prasad and Al-Keraif used spiral scan microtomography to make a 3D measurement of the spatial gap values in the cervical area and a traveling microscope to measure marginal gap at 16 equidistant points [26]. Rungruanganunt et al used micro-CT technology for 3D evaluation of precementation space by imaging ultralight body VPS impressions of the precementation space; however, with this technique marginal fit was not measured [27].…”
Section: Discussionmentioning
confidence: 99%
“…With this technique the marginal gap can easily be defined and measured, although measurements will only be carried out in the defined slices. Prasad and Al-Keraif used spiral scan microtomography to make a 3D measurement of the spatial gap values in the cervical area and a traveling microscope to measure marginal gap at 16 equidistant points [26]. Rungruanganunt et al used micro-CT technology for 3D evaluation of precementation space by imaging ultralight body VPS impressions of the precementation space; however, with this technique marginal fit was not measured [27].…”
Section: Discussionmentioning
confidence: 99%
“…24 Besides that, a parallel reported in literature concerns the association between a software tool that allows to adjust cement spacing and marginal adaptation. [25][26][27] For the CAD/ CAM E4D system (E4D Dentist system; D4D Technologies), according to Mosley et al, 25 the best spacing would be of 30 µm or 60 µm in terms of marginal maladjustment. The spacing of 50 µm is also supported in literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The spacing of 50 µm is also supported in literature. [25][26][27] Despite being still controversial, a difference can also be noticed concerning the way that tooth preparation digitalization occurs. According to Ahrberg et al, 28 direct digitalization shows a better result for marginal precision in relation to indirect ones, when a conventional mold is done and the plaster model is scanned.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The x-ray microtomography methodology 88 is the more recent and has been cited as the most appropriate method for internal fit restorations evaluation 89 allowing a threedimensional, non-destructive and non-invasive way of evaluation. 90,91 In this study, the tension tests and x-ray microtomography test values presented a positive correlation, showing that as higher the peri-implant deformation, the better the framework fit, with the opposite being true, that is, as worse the fit, less stress will arrive on bone. Other studies also reported this relationship 14,19 , in which authors state that the misadjustment may be responsible for the magnitude and distribution of stresses.…”
Section: Discussionmentioning
confidence: 57%